Tingkat Kesehatan dan Laba Bank Pembangunan Daerah di Indonesia - Muhammadinah Muhammadinah (Universitas Negeri Padang, 2021)
This study aims to determine the factors that affect the health level of BPD in Indonesia and their impact on profits. The population and sample used were 27 BPD in Indonesia with financial reports for the period 2016-2018. The analysis technique used was descriptive and multiple regression with hypothesis testing, namely the t-test and F test. The results showed that in general BPD in Indonesia was in good health except Bank Banten during the 2016 - 2018 period was in an unsanitary condition. Then Bank Papua for 2016 is in an unhealthy condition and 2017 in a fairly healthy condition. Simultaneously all the independent variables in this study have a significant effect on the health level of BPD in Indonesia. The NPL and LDR variables have a significant effect on the health level of BPD in Indonesia, while the rest do not affect it. The variable level of bank soundness has a significant and significant effect on BPD earnings in Indonesia. The implication of doing this research is that banking management, especially Regional Development Banks in Indonesia, always maintains their level of health and can account for the mandate that has been given by the community to entrust their funds.Keywords: Current Asset Ratio; Non Performing Loans; Operational Income Operational Costs; Return On Asset; Loan to Deposit Ratio; Bank Soundness Level; Profit.